relationship between folate and docosahexaenoic acid in men - Umhau, J.C; Dauphinais, K.M; Patel, S.H; Nahrwold, D.A; Hibbeln, J.R; Rawlings, R.R; George, D.T (European journal of clinical nutrition, 2006)
Objective: Docosahexaenoic acid (DHA, 22:6n-3), an essential omega 3 fatty acid, may protect against disorders of emotional regulation as well as cardiovascular disease. Animal studies demonstrate that dietary folate can increase tissue concentrations of DHA, although the literature, to date, includes no human studies examining the possibility that folate status may affect plasma DHA concentrations. The objective of this study is to determine if the blood concentrations of folate and DHA are correlated in humans. Design: Retrospective study. Setting: An American research hospital. Subjects: A total of 15 normal and 22 hostile and aggressive subjects, with a mean age of 38 years. Methods: Concentrations of plasma polyunsaturated essential fatty acids and red blood cell folate (RBC folate) were obtained prior to 1996, before American flour was enriched with folate. Results: RBC folate was significantly correlated with plasma DHA, r=0.57, P=0.005 in the aggressive group. Age, smoking and alcohol consumption did not alter the results. No other essential fatty acids were significantly associated with RBC folate in either group. Conclusions: The positive relationship between plasma DHA and RBC folate concentrations suggests that these two nutrients should be examined together in order to make the most accurate inferences about their relative contributions to disease pathogenesis. Our findings present one explanation why some conditions associated with hostility and low DHA status, such as cardiovascular disease and emotional disorders, are also associated with low folate status. Sponsorship: National Institutes of Health, National Institute on Alcohol Abuse and Alcoholism.